2012
DOI: 10.1177/0269215512462145
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy predischarge home visits for patients with a stroke (HOVIS): results of a feasibility randomized controlled trial

Abstract: Objective: To assess the feasibility of conducting a randomized controlled trial of occupational therapy predischarge home visits for people after stroke. Design: Randomized controlled trial and cohort study. We randomized eligible patients for whom there was clinical uncertainty about the need to conduct a home visit to a randomized controlled trial; patients for whom a visit was judged 'essential' were enrolled into a cohort study. Setting: Stroke rehabilitation unit of teaching hospital. Participants: One h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(79 citation statements)
references
References 13 publications
1
74
1
Order By: Relevance
“…A feasibility randomised controlled trial of occupational therapy pre-discharge home visits for patients with a stroke was completed, and has been reported elsewhere (Drummond et al, 2013). Approval was given by the Research Ethics Committee (Berkshire Research Ethics Committee ref 10/H0505/41).…”
Section: Methods Trialmentioning
confidence: 99%
See 3 more Smart Citations
“…A feasibility randomised controlled trial of occupational therapy pre-discharge home visits for patients with a stroke was completed, and has been reported elsewhere (Drummond et al, 2013). Approval was given by the Research Ethics Committee (Berkshire Research Ethics Committee ref 10/H0505/41).…”
Section: Methods Trialmentioning
confidence: 99%
“…Data were included in the analyses up to the point of withdrawal. Drummond et al (2013) primarily describe the feasibility of the trial, but also report various outcome measures and intervention costs. The treatment group received a pre-discharge home assessment visit with an occupational therapist.…”
Section: Methods Trialmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was part of The Home Visit after Stroke (HOVIS) study, in which qualitative methods were used concurrently to underpin a feasibility randomised controlled trial (RCT) which has been reported in detail elsewhere (Drummond et al, 2013). In combining qualitative approaches with the feasibility trial the objective was to identify factors which could affect the uptake of the RCT findings into clinical practice.…”
Section: Methodsmentioning
confidence: 99%